"Only Connect": A Dictum for Psychoanalysis and Life. Issue 7 (2nd October 2016) - Friedman, Henry J.
ABSTRACT: Classical psychoanalytic tradition reinforced the idea that the patient use free association and the analyst was similarly limited to a rule of free-floating attention (listening) leading to interpretation of unconscious trends. The central aim of technique was to ensure that transference of the past onto the analyst would occur in a context that could permit interpretations of the transference. This article examines ways in which therapists use psychoanalytic theory to distance themselves from the relational aspect of the therapeutic dyad. The use of the therapists' use of a professional self as a protective and distancing in the course of an analysis or therapy tends to derail the development of a successful therapeutic engagement.